Implementasi Evaluasi Sumatif pada Pembelajaran PAI di SMA Negeri 1 Mojolaban - Aditya Fachrie Zanardi Abdurrahman; Lutfian Bayu Saputra; Ahmad Najmi; Taufiq Achmad Hady (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This research aims to analyze the implementation of summative evaluation in Islamic Religious Education (PAI) learning at SMA Negeri 1 Mojolaban. Summative evaluation is carried out through written and oral tests to assess student achievement in cognitive, affective and psychomotor aspects, especially in Al-Qur'an and Hadith subjects. The research uses a qualitative descriptive method with a case study approach, collecting data through interviews, observation and document analysis. The research results show that summative evaluation is effective in assessing student achievement while identifying learning needs. Challenges that arise, such as varying abilities to memorize and read the Qur'an, are successfully overcome through individual approaches and varied evaluation strategies. This research highlights the importance of combining formative and summative evaluation to provide ongoing feedback. Recommendations include teacher training, use of technology, and collaboration with parents to increase the effectiveness of evaluation and learning.